Improving the reliability of power LEDs with diamond boards - Kyatam, Shusmitha (2022)
Despite being efficient devices, when compared to other light sources, high power light emitting diodes (LEDs) suffer from heating effects that have a negative impact on their reliability. Power LEDs are typically assembled on metal core printed circuit boards (MCPCBs) to facilitate the extraction of the heat. Diamond boards can also be used for the same purpose, since diamond is the best isotropic conductor of heat known to man and simultaneously an electrical insulator. In order to evaluate the impact of the boards on the device lifetime, high power Cree LEDs were mounted on FR4, MCPCB, and diamond boards. The case temperature was measured for different current ratings, and the aging acceleration factor of the devices mounted on FR4 and diamond boards was estimated relatively to the LEDs mounted on the MCPCB boards. Diamond boards were shown to have a tremendous impact on the lifetime; for the nominal current level, and depending on the activation energy of the aging processes, the LEDs mounted on diamond boards age 60–80 % slower than their counterparts mounted on the MCPCB boards.